Eksistensi Pegawai Pemerintah Dengan Perjanjian Kerja Ditinjau dari Peraturan Pemerintah Nomor 49 Tahun 2018 - Saputra, Deni Jaya (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2022)
Bureaucratic reform is significant for the achievement of development and excellent public services. At this time, the government issued a policy to abolish the honorary system and replace it with government employees under a work agreement (PPPK). The presence of PPPK as a civil servant (ASN) is to increase employee resources professionally and competently so that they can keep up with the times and apply various technology applications. PPPK is also entitled to a salary and several allowances as regulated in Article 4 Section 2 of Presidential Regulation Number 98 of 2020 concerning First Personnel Salaries and Allowances. Its states that the PPPK allowance consists of: a. family allowance; b. food allowance; c. structural position allowance; d. functional position allowance; or e. other allowances.